2017
DOI: 10.1007/s00027-017-0527-2
|View full text |Cite
|
Sign up to set email alerts
|

The trapping of organic matter within plant patches in the channels of the Okavango Delta: a matter of quality

Abstract: The trapping of organic matter w ithin plant patches in the channels of the Okavango Delta : a matter of quality Aquatic sciences : a multidisciplinary journal for theoretical and applied limnology, fisheries science and w ater technology / Centrum voor Wiskunde en Informatica, Amsterdam. Department of Algebra, Analysis and Geometry -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…BSi accumulation in vegetation varied per lagoon and was dependent on plant species dominance [see Prychid et al (2003) and Hodson et al (2005) for BSi contents in plants related to their phylogenetic position]. The BSi stock in macrophytes ranged from 0.054 to 0.288 t BSi ha −1 , which is situated between values reported for submerged macrophytes in the Okavango Delta channels (0.008 t BSi ha −1 ; Schoelynck et al, 2017) and values reported for emergent wetland vegetation in the Okavango Delta (ranging from 0.010 to 1.600 t BSi ha −1 ; Struyf et al, 2015). The highest BSi concentrations were found in macrophytes collected from Kodjoboue lagoon and were related to the dominance of emergent species (A. zizanioides, B.…”
Section: The Role Of Macrophytes and Diatoms In Lagoon Bsi Storagementioning
confidence: 98%
See 1 more Smart Citation
“…BSi accumulation in vegetation varied per lagoon and was dependent on plant species dominance [see Prychid et al (2003) and Hodson et al (2005) for BSi contents in plants related to their phylogenetic position]. The BSi stock in macrophytes ranged from 0.054 to 0.288 t BSi ha −1 , which is situated between values reported for submerged macrophytes in the Okavango Delta channels (0.008 t BSi ha −1 ; Schoelynck et al, 2017) and values reported for emergent wetland vegetation in the Okavango Delta (ranging from 0.010 to 1.600 t BSi ha −1 ; Struyf et al, 2015). The highest BSi concentrations were found in macrophytes collected from Kodjoboue lagoon and were related to the dominance of emergent species (A. zizanioides, B.…”
Section: The Role Of Macrophytes and Diatoms In Lagoon Bsi Storagementioning
confidence: 98%
“…The carbon occluded in the phytoliths of wetland plant species potentially even forms an important sink to consider in the carbon cycle (Li et al, 2013). Exemplary to this is the strong (permanent) silica sink in the Okavango Delta sediments (Botswana) that can be associated with a dominance of silica-rich tropical giant-grasses such as Cyperus papyrus L. (Struyf et al, 2015;Mosimane et al, 2017;Schoelynck et al, 2017). BSi accumulation in macrophytes, and thus potentially in sediments, varies strongly between species.…”
Section: Introductionmentioning
confidence: 99%
“…Tussocks of wetland sedges efficiently retain biogenic silica, giving them a competitive advantage (Opdekamp et al, 2012). In the Okavango delta, aquatic macrophytes accumulate and concentrate organic matter in sediments below patches, allowing high productivity in an otherwise oligotrophic environment (Schoelynck et al, 2017). Liu et al (2017) also found this 'soil island' effect around isolated and clustered tamarisk (Tamarix chinensis Lour.)…”
Section: Solutesmentioning
confidence: 99%
“…Rooted macrophytes act as "ecosystem engineers" for N removal (Jones, Lawton, & Shachak, 1994;Vila-Costa et al, 2016) by influencing denitrification in several ways: for example, by (i) increasing organic matter accumulation (i.e. root exudates, decaying plant biomass, trapped suspended material), thus providing labile organic carbon whose mineralization promotes anoxic conditions (Hang et al, 2016;Schoelynck et al, 2017;Taylor, Moore, & Scott, 2015); (ii) releasing oxygen in the rhizosphere and establishing oxic−anoxic interfaces where the coupling of aerobic and anaerobic processes (such as organic N mineralization, nitrification, and denitrification) occurs (Rehman, Pervez, Khattak, & Ahmad, 2017;Soana et al, 2015); and (iii) promoting microbial population growth and diversity through the provision of submerged surfaces (e.g., stems and leaves) available for colonization (Soana, Gavioli, et al, 2018;Toet, Huibers, Van Logtestijn, & Verhoeven, 2003). Denitrification results in permanent removal of bioavailable N. Thus, assessing this process is a pivotal scientific and management task for decreasing eutrophication of aquatic ecosystems in human-impacted watersheds.…”
Section: Introductionmentioning
confidence: 99%